The ‘Asklepieion’ of Pergamum in the century II CE as a place of temporal, spatial and identity interpenetration - Guerra, Lolita Guimarães (Romanitas - Revista de Estudos Grecolatinos, 2015)
The Pergamene Asklepieion in Asia Minor was in the Second Century C.E. a destination to travellers from all over the Roman Empire. There, they enjoyed many practices that went beyond devotional and medical needs. After the visiting of Hadrian to the city, a broad rebuilding of the sanctuary took place, in which the architectural structures, aesthetic models, and figurative representations within the sanctuary inspired a profound identification between Pergamene traditions and Rome. At the same time, the variety of experiences in the Asklepieion gave the visitors opportunity to the reconstruction of identities and relationships. In this paper, we shall discuss how the uses of the sanctuary in the Second Century C.E. distinguished it as a place that surpassed identities, spatialities and temporalities.
Keywords: Early Roman Empire; Pergamene; Asklepieion; Cult of Asklepios; Travelling